“WHO am I?”: A Comparative Metadiscourse Analysis of Identity and Self-construction on LinkedIn Profiles and X Bios - Bukola Alfred (Journal of linguistics, culture and communication, 2025)
This research presents a comparative metadiscourse analysis of LinkedIn profiles and X bios for Identity and Self-construction. The study identifies the various metadiscourse features employed in LinkedIn profiles and X bios, categorizes the features, and also discusses how the identified features are used to construct professional and personal identities on LinkedIn and X. The study unveils how individuals strategically construct identities for themselves and establish connections, through linguistic and rhetorical strategies. The research qualitatively analyzes 60 accounts each on LinkedIn and X. Hyland’s (2005) Metadiscourse theory is adopted as the framework for the study. The data findings reveal differences in language use, self-presentation strategies, and how users establish their personal or professional identity and presence on both online platforms. It also reveals that X bios emphasize creativity, humor, and personal interests. In contrast, LinkedIn profiles prioritize professionalism, accomplishments, and career-related information. The study concludes that a comparative metadiscourse analysis of LinkedIn profiles and X bios reveals a distinct use of metadiscourse markers for identity and self-construction, highlighting how individuals tailor their self-presentation toward the platform's conventions and purposes. This highlights the dynamic nature of self-presentation in the digital age.